Computational Fluid Dynamic Analysis of a Heater Chimney with and without a Flow Straightener - Scarabino, Ana Elena (2015)
International standards for control of pollutants and particulate flow into the atmosphere require periodically monitoring of gases in discharge chimneys. For acceptable control, the streamlines must be straight, inclined by no more than a few degrees from vertical. A common problem is the occurrence of cyclonic flow, i.e. flow organization in one or more longitudinal vortices. The strong rotational velocity component makes the streamlines helical, invalidating conventional speed measurements with pitot tubes or other methods, which can be sensitive to sensor misalignment with the flow. This work presents a numerical analysis of the flow within and outside a chimney of low length/diameter ratio with a lateral inlet for combustion gases, the gases dispersion in the atmosphere, the problematic flow configuration detected and a flow straightener proposed to reduce the vorticity within the chimney, which reduces the streamlines deviation from 35-40° to less than 5°.